Hybrid Intelligent Warning System for Boiler tube Leak Trips - Singh D.; Ismail F.B.; Shakir Nasif M. (EDP Sciences, 2023)
Artificial intelligence; Boilers; Coal; Fossil fuel power plants; Genetic algorithms; Intelligent systems; Learning systems; Neural networks; Thermoelectric power plants; Artificial intelligent; Coal-fired power plant; Detection and diagnosis; Extreme learning machine; Hybrid intelligent system; Reliable monitoring systems; Thermal power plants; Training algorithms; Monitoring